PENGARUH TRICHODERMA SP. DAN LAMA PEMANASAN MATA TUNAS (BUD CHIPS) TEBU TERHADAP PERTUMBUHAN AWAL BENIH TEBU VARIETAS 864 - HARYUNI HARYUNI (JURNAL ILMIAH AGRINECA, 2012)
The object of this research was examine to determine the effect of application Trichoderma sp and Hot Water Treatment (HWT) on the resistance and health of sugarcane seed buds. Reproduction of Trichoderma sp. performed in the laboratory center of Protection plantation Central of Java in Salatiga, Buds cip of seeds from garden in Boyolali. Multiplication in the green house of Protection Laboratory analysis at the Faculty of Agriculture Development, University of Tunas Pembangunan Surakarta. The experiment was arranged in a completely randomized factorial design, consisted of two factors. The first factor was Trichoderma sp inoculation wich were T1 = 25 g and T2 = 50 g and not inoculation of sugarcane seedling. The second factor was variation of plant hot water treatment, which were P0 = 0 minute, P1 = 30 minute, P2 = 60 minute, and P3 = 90 minute. Each treatment was repeated three times and each replicate consisted of 10 plants. The result showed that that the inoculation of Trichoderma sp. 25 g and variations hot water for 60 minutes increases the resistance and health of sugarcane seedlings show that increase plant growth of sugarcane seedlings variety 864.